Towards truly sustainable IoT systems: the SUPERIOT project - Marcos Katz; Tuomas Paso; Konstantin Mikhaylov; Luis Pessoa; Helder Fontes; Liisa Hakola; Jaakko Leppäniemi; Emanuel Carlos; Guido Dolmans; Julio Rufo; Marcin Drzewiecki; Hazem Sallouha; et al. (JPhys Photonics, 2024)
This paper provides an overview of the SUPERIOT project, an EU SNS JU (Smart Networks and Services Joint Undertaking) initiative focused on developing truly sustainable IoT systems. The SUPERIOT concept is based on a unique holistic approach to sustainability, proactively developing sustainable solutions considering the design, implementation, usage and disposal/reuse stages. The concept exploits radio and optical technologies to provide dual-mode wireless connectivity and dual-mode energy harvesting as well as dual-mode IoT node positioning. The implementation of the IoT nodes or devices will maximize the use of sustainable printed electronics technologies, including printed components, conductive inks and substrates. The paper describes the SUPERIOT concept, covering the key technical approaches to be used, promising scenarios and applications, project goals and demonstrators which will be developed to the proof-of-concept stage. In addition, the paper briefly discusses some important visions on how this technology may be further developed in the future.